(untitled) (Fiep Bulletin - online, 2017)
Initially two points of view are taken into account in the development of the human being; The intellectual being and thebeing body, emphasizing that the human being in its totality is a social being, that has the capacity to adapt to certain parametersimposed by the society and thus to fit in its surroundings.Within these processes of adaptation in society man has been creating questions about his existence and abouthimself adapting the knowledge acquired in supported theories and sciences with paradigms found on the environment thatsurrounds him, discovering himself in a duality between body and soul, And in turn trying to break that duality.It can also be found that within the intellectual and corporal development of man we spend our lives trying to find ouressence, that which makes us feel that we have an identity in the world and that we have a logical reason to exist, observing thatlife is a transport Of moments that for man can become so valuable as to find the answer to his reason as a human being.